The essential Sopranos reader (Essential readers in contemporary media and culture, 2011)
Introduction -- The Sopranos, David Chase, HBO, and television. The Sopranos as tipping point in the second coming of HBO / Gary R. Edgerton -- From made men to Mad men: what Matthew Weiner learned from David Chase / David Lavery -- The Sopranos: if nothing Is real, you have overpaid for your carpet / Martha P. Nochimson -- Author(iz)ing Chase / Robin Nelson -- Characters. "Half a wiseguy": Paulie Walnuts, meet Tom Stoppard / Paul Wright -- Christopher, Osama, and A.J.: contemporary narcissism and terrorism in The Sopranos / Jason Jacobs -- "When it comes to daughters, all bets are off": the seductive father-daughter relationship of Tony and Meadow Soprano / Marisa Carroll -- Gendering The Sopranos. "Blabbermouth cunts", or, speaking in tongues: narrative crises for women in The Sopranos and feminist dilemmas / Kim Akass and Janet McCabe -- Honoring the social compact: the last temptation of Melfi / Nancy McGuire Roche -- A "finook" in the crew: Vito Spatafore, The Sopranos, and the queering of the Mafia genre / George De Stefano -- Cinematic Concerns. The producers: the dangers of filmmaking in The Sopranos / Cameron Golden -- Comfortably numb? The Sopranos, new brutalism, and the last temptation of Chris / Glen Creeber -- -- dreams and therapy. fishes and football coaches: the narrative necessity of dreams in the sopranos / Cynthia Burkhead -- From here to InFinnerty: Tony Soprano and the American Way / Terri Carney -- "Whatever Happened to Stop and Smell the Roses?": The Sopranos as anti-therapeutic narrative / David Pattie -- Ethnic and Social Concerns. Mangia Mafia! food, punishment, and cultural identity in The Sopranos / Michael M. Grynbaum -- The guinea as tragic hero: the complex representation of Italian Americans in The Sopranos / Frank P. Tomasulo -- "All Caucasians look alike": dreams of whiteness at the end of The Sopranos / Christopher Kocela -- Images of justice and The Soprano